Students' readiness for and perception towards inter-profesional learning: a cross sectional study - Mohamed Nazar, Nor Ilyani; Ab Salam, M. G.; Abibullah, M.A.; Md Taib, M. F.; Alauddin @ Muhd Zahir, SNF; Syed Omar, Syed Huzaifah; Abdul Rashid, N. F.; Abdul Hamid, A. N.; Mustapa, N. T.; Elkalmi, Ramadan Mohamed Mahmod (Malaysian Pharmaceutical Society, 2015)
Current healthcare related issues and problems are becoming more complex. Comprehensive patient care is impossible to be achieved by clinicians alone as this requires inter-rofessional approach in the management. Therefore, it has been suggested that students in healthcare profession should be exposed to inter-professional learning (IPL) during their undergraduate years. The objectives of this study were to investigate the readiness for and the perception of IPL among healthcare professional students of International Islamic University Malaysia (IIUM).Data was collected using an established questionnaire namely, Readiness for Inter-professional Learning Scale (RIPLS) which was distributed to final year students of 3 main programmes; Medicine, Pharmacy and Nursing. Out of the 122 students, a majority denied being exposed to IPL. Teamwork and collaboration showed the highest mean (40.2 + 4.18) that the students highly agreed on. Female students have significantly lower negative professional ID compared to the male students (p = 0.011). This subdomain also exhibited significant difference in scores between cGPA results of the students. Students with high cGPA (3.50-4.00) tended to have lower negative attitude towards IPL crossing programmes (p = 0.009). Those who have exposure to IPL show significant positive attitudes towards IPL regardless of the programme (p = 0.032). The study shows that students from the medical programme have the least exposure to IPL. Gender and cGPA status of students may also play an important role in determining their attitude towards IPL. There are still rooms for improvement to nurture readiness among the students.